EFL students' attitudes of using task-based speaking activities - Huỳnh Thị Ngọc Ảnh (Trường Đại học Trà Vinh, 2021)
The intent of this study was to examine how task-based speaking activities were used in speaking lessons of the pilot textbook (Tieng Anh 10), as reported by rural high school students. The students’ views were elaborated into two aspects: their awareness and their attitudes. Concerning awareness, the study aimed to find out the extent to which students had the knowledge of the TBSAs that were put into use by their teachers in speaking lessons. In other words, the researcher attempted to examine the types of TBSAs that to verify whether the types of TBSAs were implemented in EFL classes and how much they knew about TBSA in the MOET-based speaking lessons. Secondly, the study aimed at finding out the students’ attitude towards the TBSA. The term ‘attitude’ used in this study was drawn from Gardner’s (1985), who suggests that ‘attitude’ can refer to affective and cognitive factors (p. 8). As such, the concept ‘attitude’ was understood as preferences and perceptions in this study. While preferences involve ‘likes’ and ‘dislikes,’ the cognitive factor that the study aimed at was to find out how positive students had concerning the usefulness of TBSAs. It might be expected there would be some TBSAs that students had negative evaluations.